Improperly diagnosed odontogenic myxoma in a 23-year-old female: A radiographic analysis - Sugianto, Gabriel Maria Ferdilia; Nurrachman, Aga Satria; Astuti, Eha Renwi (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Misdiagnosis can occur due to various radiographic alterations linked to odontogenic myxoma (OM). Regular examination can detect abnormalities early on, but not all practitioners are aware that these lesions exist. Purpose: This case report aims to describe and discuss an OM case from the perspective of oral radiology on panoramic radiographs and cone-beam computed tomography (CBCT). Case: A 23-year-old female went to her first dentist for orthodontic treatment with no prior radiographic evaluation. On January 7th, 2022, the second dentist extracted teeth 38 and 48 using the panoramic radiograph without identifying lesions. Concerned about swelling on her lower right gingiva, which had gradually grown, the patient went to an oral and maxillofacial surgeon on November 15th, 2022. The clinical examination revealed facial asymmetry with a thick, palpable, firm mass with an ambiguous boundary. Despite the evident movement of tooth 47, the gingiva exhibited no noticeable change in coloration. Case management: From the panoramic examination, multilocular radiolucency with radiopaque septa and aggressive mass characteristics were found. Advanced imaging CBCT was used to investigate further and correlate histology findings for treatment. Conclusion: Odontogenic myxoma is difficult to distinguish from other benign and malignant neoplasms due to the wide variations of radiological patterns. Cone-beam computed tomography provides a thorough and broad range of data that can be used to make a precise diagnosis and develop an effective treatment strategy. This highlights the critical need for a trained expert to thoroughly examine CBCT scans.